The socio-spatial logic of favela: patterns of self-organized informality - Loureiro, Vânia Raquel Teles (2019)
The present work analyzes the configuration of the favela from its socio-spatial patterns, seeking to understand the phenomenon in its global scale. It adopts the Social Logic of Space (Space Syntax) as theoretical, methodological and technical approach, allowing the reading of the object in its spatial complexity. A total of 120 settlements located around the world are compared, using a set of 26 configurational variables (between qualitative and quantitative, geometric and topological). The results are also compared to a sample of 45 Portuguese cities of medieval origin (exemplars of the organic city) and by Medeiros research for 44 Brazilian cities (2013) (illustrative of contemporary urban structures). The research questions are considered: is there a favela spatial pattern? and to what extent the favela reproduces spatial patterns inherent to the organic and historically consolidated city? The research is based on the hypothesis that the favela configuration reveals spatial patterns derived from its self-organizing practices, which are responsible for successful urban dynamics. The findings reveal that the favela is organized within the larger system that receives it, sharing a common and transversal logic in the various regions of the world, despite its varied cultural contexts. There were also found common patterns in organic cities and favelas, revealing similar processes of development